If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + 6n = -80 Solving -2 + 6n = -80 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 6n = -80 + 2 Combine like terms: -2 + 2 = 0 0 + 6n = -80 + 2 6n = -80 + 2 Combine like terms: -80 + 2 = -78 6n = -78 Divide each side by '6'. n = -13 Simplifying n = -13
| 4x=2x+19 | | ag-14=2g | | 5(x+2)+8=28 | | 49x^2=28x-4 | | 6x^2-15x+14x-35=0 | | 2(x+5)+7=19 | | 5x+4=3x+2 | | -2+6n=-8 | | 3(x+4)+8=2 | | 4x^2=81 | | 55=5(2x+3) | | x^2+8x=-16 | | 12(3x-2)=3(12x+4) | | 42=3(4x+2) | | y=x+45-90 | | 51-0.5p=2.5p | | -(7y+2)-(-6y-6)=-3 | | 3(2x+7)=-29+44 | | 36a^2-4=0 | | (x-6)(3x+4)=-11 | | 0=320x-.1x^2 | | 26=2(5x+3) | | 5x-2(3x+5)=32 | | 9a-3=2a+11 | | 3(5+3m)-8=88 | | 92-20=9x | | y=3x^2+6x-9 | | 138=-2+7r | | 4x+5=41 | | 30-10=5x | | 8=-2x-12 | | 6(4x-5)=2(12x+4) |